Las energías renovables como oportunidad y desafío para el desarrollo territorial Valle de Lerma, Salta, Argentina - Belmonte, Silvina (2013)
Renewable energy assessment arises in the context of Territorial Planning of Lerma Valley in Salta as a strategy for regional development and improved quality of life and environment. The methodology applied is based on Multi- Criteria Evaluation tools, Geographic Information Systems application and participatory consultation techniques. The results were oriented to territorial diagnosis, energy resources assessment and alternative technologies as well as planning and management proposals. At diagnosis, renewable energies were identified as viable options in production and access to basic services. The potential offer of renewable resources was high as to solar radiation and hydraulic resources but moderate as to wind potential. It was varied in the case of organic energy and biomass due to multiple sources. Technological alternatives and actions to improve the energy scenario in Lerma Valley were assessed and the following priorities were established: environmental education, strategic energy planning and varied applications of solar energy (dryers, greenhouses, bioclimatic architecture, water collectors and cookers). Energy policies that are ‘more’ sustainable were suggested, such as: coordinating the energy sector with both other sectors and action levels within the framework of an integrated land use planning, strengthening local institutions for energy management, and overcoming limitations on local transfer of renewable energy. Renewable energies should be considered as an opportunity and challenge to promote processes of ‘change’ in the region through a reaffirmed commitment to environment and society.